(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
Emotional suppression and cognitive barriers in emotional expression remain complex fundamental problems of modern clinical and social psychology. The dynamics of analytical data show that systematic concealment of internal experiences not only negatively affects social adaptation and interpersonal communication but also creates a fertile basis for deep psychosomatic changes and the clinical development of alexithymia. A comprehensive psychodiagnostic analysis was conducted on a representative sample at Gulistan State University to explore these hidden psychological mechanisms. International methodologies were used to meticulously assess the level of emotional intelligence, self-awareness, and affective regulation strategies among young adults. Empirical correlation analysis confirmed a strong direct link between suppressing emotions due to fear of social condemnation and severe interpersonal anxiety. Sociocultural factors, including childhood emotional invalidation and restrictive gender stereotypes, were identified as the key cognitive determinants of the "psychology of silence" among youth. The findings emphasize the urgent need for targeted psychological interventions to foster emotional openness and resilience.